KETIDAKPASTIAN PDSS DAN IMPLIKASINYA TERHADAP KURIKULUM 2025 - Nabila, Aisyah; Dwiyanti, Agustina; Permana, Dzaki; Mariyah, Siti (CENDEKIA: Jurnal Ilmu Pengetahuan, 2025)
This study examines the implementation of inclusive education within the Merdeka Curriculum framework and the challenges of implementing the 2025 Curriculum, using a descriptive qualitative method based on literature studies. The main findings identify the uncertainty of the School and Student Database (PDSS) system as a serious obstacle to the 2025 Curriculum, including issues of validity, input, and data updates that hinder accountability and data-based decision making, including university selection. The implication is that the goal of the 2025 Curriculum to realize flexible, differentiated, and inclusive learning is threatened to fail to be achieved optimally without the support of strong and reliable data infrastructure. It is concluded that education data reform is a crucial urgency. Recommendations are emphasized on strengthening the PDSS system through integrated technology, operator training, periodic data monitoring, and aligning data policies with curriculum policies to ensure the success of the proposed education reform. ABSTRAKPenelitian ini mengkaji implementasi pendidikan inklusif dalam kerangka Kurikulum Merdeka serta tantangan implementasi Kurikulum 2025, menggunakan metode kualitatif deskriptif berbasis studi literatur. Temuan utama mengidentifikasi ketidakpastian sistem Pangkalan Data Sekolah dan Siswa (PDSS) sebagai kendala serius bagi Kurikulum 2025, mencakup masalah validitas, input, dan pembaruan data yang menghambat akuntabilitas serta pengambilan keputusan berbasis data, termasuk seleksi perguruan tinggi. Implikasinya, tujuan Kurikulum 2025 untuk mewujudkan pembelajaran yang fleksibel, terdiferensiasi, dan inklusif terancam gagal tercapai secara optimal tanpa dukungan infrastruktur data yang kuat dan terpercaya. Disimpulkan bahwa reformasi data pendidikan menjadi urgensi krusial. Rekomendasi ditekankan pada penguatan sistem PDSS melalui teknologi terintegrasi, pelatihan operator, pemantauan data secara berkala, serta penyelarasan kebijakan data dengan kebijakan kurikulum untuk menjamin keberhasilan reformasi pendidikan yang diusung.